1995
DOI: 10.1007/bf00010477
|View full text |Cite
|
Sign up to set email alerts
|

Competition for ammonium between plant roots and nitrifying and heterotrophic bacteria and the effects of protozoan grazing

Abstract: The competition for limiting amounts of ammonium between the chemolithotrophic ammonium-oxidizing species Nitrosomonas europaea, the heterotrophic species Arthrobacter globiformis and roots of Plantago lanceolata (Ribwort plantain) was studied in a series of model systems of increasing complexity, i.e. energy-limited continuous cultures, non-water-saturated continuously percolated soil columns and pots with "7-sterilized soil planted with axenic P. lanceolata seedlings. The effects of bacterial grazing by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
57
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 32 publications
4
57
0
Order By: Relevance
“…These bacteria obtain energy for growth from the oxidation of ammonia and acquire the majority of their carbon through the fixation of CO 2 via the Calvin cycle. Since these microorganisms must compete with plants and other microorganisms that assimilate ammonia for biosynthesis (47,48), it is likely that they have developed adaptive strategies to cope with periods of ammonia starvation. Both Nitrosomonas cryotolerans and Nitrosomonas europaea have been shown to be particularly resilient to energy source deprivation.…”
mentioning
confidence: 99%
“…These bacteria obtain energy for growth from the oxidation of ammonia and acquire the majority of their carbon through the fixation of CO 2 via the Calvin cycle. Since these microorganisms must compete with plants and other microorganisms that assimilate ammonia for biosynthesis (47,48), it is likely that they have developed adaptive strategies to cope with periods of ammonia starvation. Both Nitrosomonas cryotolerans and Nitrosomonas europaea have been shown to be particularly resilient to energy source deprivation.…”
mentioning
confidence: 99%
“…AOB often live in close proximity to nitrite-oxidizing bacteria and together they convert the most reduced form of nitrogen (NH 4 ϩ ) to the most oxidized (NO 3 Ϫ ) (40). In nature, AOB often face longer periods of NH 4 ϩ starvation and limitation due to low nitrogen input, low mineralization rates, or competition with other AOB (8), heterotrophic bacteria (48, 49), or plants (5,6,50). In order to respond rapidly when NH 4 ϩ becomes available, AOB must maintain their ability to oxidize NH 4 ϩ during these periods.…”
mentioning
confidence: 99%
“…On the other hand, aquatic plants assimilate and incorporate inorganic nitrogen into organic matter and a significant part of this nitrogen can be supplied from the sediment (Short and McRoy 1984;Caffrey and Kemp 1992;Pedersen and Borum 1992). The plant therefore competes with nitrifying and denitrifying bacteria for nitrogen, and recent results have shown that roots of angiosperms may be better competitors than nitrifiers for NH,+ in the sediment (Verhagen et al 1995). Whether the presence of rooted aquatic plants stimulates or reduces bacterial nitrification-denitrification activity will depend on the balance between these opposing effects of root 0, release and root N uptake.…”
mentioning
confidence: 99%